Training on Making Biscuits from Moringa “Utilizing Moringa” to Grow Creative Economy in Bulukandang Village Community, Prigen District, Pasuruan Regency: Pelatihan Pembuatan Biskuit dari Kelor “Pemanfaatan Moringa” untuk Menumbuhkan Ekonomi Kreatif Pada Masyarakat Desa Bulukandang Kecamatan Prigen Kabupaten Pasuruan - Amalia , Nur Faizzatul; Akbar , Ali; Masruroh , Indah; Putri , Sinta Cahyani; Giri , Fauzi Rachman (Universitas Muhammadiyah Sidoarjo, 2022)
Moringa is one of the plants that has a high nutritional content and the leaves can be used as one of the basic ingredients for processing food or drinks. The process of making Moringa biscuits produces Moringa flour which in general, Moringa leaves have not been utilized properly in the community. Moringa flour is the result of filtering dried Moringa leaves. The community service activities that have been carried out aim to provide knowledge to the community about processing Moringa leaves into biscuits. This activity was carried out through the extension method by providing a material related to the introduction of Moringa products and their nutritional value, as well as providing direct training in making Moringa biscuits. The process of processing Moringa biscuits aims to increase public awareness regarding the benefits of Moringa leaves and it can improve the creative economy of the Bulukandang Village community.